Poliovirus returns to Pakistan: A rising concern. (August 2022) - Imran, Laiba; Rehan, Syeda Tayyaba; Cheema, Huzaifa Ahmad; Hasan, Mohammad Mehedi
Abstract: Poliomyelitis is a completely preventable but deadly virus causing paralysis in children and in some cases, death. Pakistan is one of the only two countries where polio is still prevalent despite relentless vaccination drives. In the past two months, four cases of polio have been documented in children no older than two years, condemning them to a life of disability. This commentary explores the reasons for the recent spike in polio cases and what measures can be taken to limit the spread of the disease, especially in high-risk areas where vaccine hesitancy poses a major problem. Unless drastic measures are taken by the healthcare sector, polio will continue to be a burden on the country's economy and countless more children will fall victim to the disease.